Influence of concurrent and functional training on miR-1/miR-126 gene expression and cardiovascular function in postmenopausal women - Majid Kashef; Fereshte Shahidi; Hadi samadi; Leyla Golroo (Journal of Exercise & Organ Cross Talk, 2023)
It is becoming more important to understand the physiological processes that contribute to the emergence of risk factors associated with menopause, and to discover strategies for preventing and reversing them. The current research aimed to determine the impact of functional and concurrent training on miR-126/miR-1 gene expression, and cardiovascular function in middle-aged postmenopausal women. In this study, 24 women between the ages of 50 and 60 years old with a sedentary life style participated. The subjects were randomly divided into the control group, concurrent training group, and functional training group. The Control received no intervention, and the experimental groups performed selected training protocols for 12 weeks. Doppler ultrasound graphs were utilized after the interventions to evaluate the cardiovascular function. Also, 48 hours after experiment, the blood collection was taken to assess miR-126/miR-1 gene expression. To compare the variables, one-way ANOVA test followed by Tukey's post hoc test was used. The significance level was set at p < 0.05. The results showed that the training programs led to significant enhancements in FLOW-mediated dilation, and PSV (peak systolic velocity). Moreover, there was a significant decrease in the vascular stiffness in the participants after undergoing the training. Additionally, miR-1 and miR-126 gene expression were found to be increased in response to both training interventions. These findings suggest that concurrent and functional training may be an effective approach for reducing the risk of age-related diseases in menopausal women through promoting cardiovascular functions and miR-126/miR-1 gene expression elevation.